Comparison of Antioxidant Activity Test of Red Dragon Fruit Extract 70% Ethanol Solvent and 96% Ethanol - Anak Agung Ayu Niti Wedayani; Ni Ketut Susilawati; Eka Arie Yuliyani; Wiguna, I Made Danuarta; Restuningdyah, Novia Andansari Putri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Super Red Dragon Fruit is known to have various compounds with high antioxidant activity, which are important in preventing or assisting therapies to reduce free radicals in the body. Different types of solvents, including ethanol, can affect the antioxidant levels in dragon fruit compounds. Therefore, it is important to determine the level of ethanol solvent that provides the highest antioxidant activity. This study aims to evaluate the antioxidant activity in red dragon fruit extract using 70% and 96% ethanol solvents and determine whether there is a difference in activity between the two. Using the true experimental method, antioxidant activity in the fruit and skin of red super dragon fruit extracted using two different solvent levels was compared. Based on the shapiro-wilk test which showed a p value of 0.410, it was found that there was no significant difference between the two solvents in terms of antioxidant activity. This result indicates that the antioxidant activity in red dragon fruit extracts with 70% and 96% ethanol solvents has no significant difference.